Barriers to Customer Integration into New Product Development Process: A Case of Apparel Industry in Pakistan - Muhammad Ali Sheikh; Dr. Hayat Awan (International Journal of Supply Chain Management, 2013)
In recent years,multinationals developed close relationship with customers by integrating theminto NPD process which reduced switching and increased satisfaction. While SMEsfaced severe breakdowns due to product failures led by customerdissatisfaction. A reason for this switching is prohibition of customerintegration into NPD process. Within this context, the objective is to identifythose potential reasons which become the source of non-integration. Data forthis study was derived for a survey carried out in 25 SMEs (apparel). Anexploratory factor analysis, correlation analysis, ANOVA and descriptive statswere utilized to discover the potential of various barriers. Out of allbarriers, lack of awareness, trust and compatibility were potential barriersfound positively related with non-integration. Non/less experienced firmsshowed lack of awareness which led them to lack of trust while experiencedfirms lacked flexibility in integrating customers. Locally operating SMEsshowed lack of awareness and trust while firms at regional level were foundmore aware but refused the importance of integration. This study is focusing oncustomer integration into the SMEs sector has many implications forprofessionals and organizations.